Protective mechanisms of three antioxidants against T‐2 toxin‐induced muscle protein deterioration in shrimp. (15th March 2022) - Huang, Xiaoyue; Huang, Zhanrui; Sun, Lijun; Qiu, Mei; Deng, Qi; Fang, Zhijia; Wang, Yaling
Abstract: BACKGROUND: Quercetin (Q), tea polyphenols (TP), and rutin (R) are widely used plant‐derived active ingredients. They possess antioxidant, anti‐inflammatory, and anti‐tumor properties, and can reduce the muscle damage caused by mycotoxins. However, few studies have examined the protective mechanisms of quercetin, tea polyphenols, and rutin on muscle quality. To elucidate their protective mechanisms, shrimp were exposed to both T‐2 toxin and these three antioxidants for 20 days in a dose‐escalating trial. The changes in the protein composition of shrimp muscle were measured. The target proteins associated with T‐2 and antioxidants were screened and identified by non‐labeled quantitative proteomics. RESULTS: The T‐2 toxin induced abnormal expression of 21 target proteins, leading to the deterioration of muscle proteins in shrimp. The three antioxidants ameliorated the T‐2 toxin‐induced damage to muscle proteins by increasing the sarcoplasmic and myofibrillar protein content and decreasing the alkali‐soluble protein content. Quercetin had the strongest protective effect. The protective processes of these antioxidants involved the upregulation of target proteins involved in carbohydrate metabolism (enolase, malate dehydrogenase), protein translation (elongation factor 1‐alpha and eukaryotic translation initiation factor 2 subunit alpha), and cytoskeleton component (actin 2, fast‐type skeletal muscle actin 1). Quercetin regulated the largest number of target proteins, making it the best protective agent against T‐2 toxin. CONCLUSION: The T‐2 toxin (4.80–24.30 mg/kg feed) induced changes in target proteins and muscle composition of shrimp, leading to a deterioration in muscle proteins. Quercetin (2.00–32.00 g/kg feed) had significant protective effects against this deterioration in muscle protein in shrimp. © 2022 Society of Chemical Industry.